The global financial crisis impact on higher education - Hunter, Susan J. (Emirates lecture series, 2013)
"In this paper, we examine how the financial crisis has affected higher education, in each case looking first at the United States in general and then specifically at the University of Maine. We also briefly examine the impacts in Europe and Asia. The consequences for higher education are not isolated, but rather are a piece of the interrelated cross-sector crisis. In the same regard, the impact of the financial crisis on higher education has affected other aspects of the financial system, for instance the degree of student indebtedness."--Introduction.